Antimicrobial Activity of Cariniana legalis (Lecythidaceae) Seedlings Subjected to Different Light Intensities (Revista Brasileira de Plantas Medicinais, 2020)
Cariniana legalis, Lecythidaceae is an emergent species endemic to the Brazilian Atlantic Rainforest. Popularly known as jequitibá-rosa, this sapwood has been used in reforestation, and in folk medicine to treat leucorrhoea, female reproductive disorders and back pain. The aim of this study was to evaluate the in vitro antimicrobial activity of the aqueous extract of leaves of C. legalis seedlings subjected to different light environments, in shade houses. From the leaves, the aqueous extracts were made by means of decoction and lyophilization. The antifungal and antibacterial activity against the fungi Candida albicans, C. krusei and C. parapsilosis and the bacteria Escherichia coli and Staphylococcus aureus were evaluated. The minimum inhibitory concentration and minimum fungicidal/bactericidal concentration were determined. The results revealed that the aqueous extracts of leaves of C. legalis seedlings have bacteriostatic action for E. coli and fungicidal activity against C. krusei and C. parapsilosis. Our results suggest the antimicrobial action of anthocyanins produced under higher light radiation in the extracts of C. legalis leaves. However, further studies are needed to characterize with accuracy the substances responsible for the antimicrobial activity.